2010
DOI: 10.1109/lawp.2010.2089967
|View full text |Cite
|
Sign up to set email alerts
|

Fade Slope Statistics on a Slant Path at 50 GHz

Abstract: Statistics of fade slope at 50 GHz have been derived from one year of slant path attenuation measurements, using time interval lengths between 2 and 200 s. From these statistics, the dependence of fade slope on the attenuation level and time interval can be quantified. It has been found that the ITU-R model, specified for frequencies up to 30 GHz, fits well the experimental conditional distributions. Nevertheless, some divergences are observed for the lowest attenuations, which may be attributed to cloud effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…The following observations are noted. First, all the fade slope distributions here are symmetric around 0 dB/s which confirm the finding of other researchers [14, 16–19, 21]. Second, all the CPDFs follow normal distribution with zero average.…”
Section: Results and Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…The following observations are noted. First, all the fade slope distributions here are symmetric around 0 dB/s which confirm the finding of other researchers [14, 16–19, 21]. Second, all the CPDFs follow normal distribution with zero average.…”
Section: Results and Analysissupporting
confidence: 90%
“…Both found that the ITU-R model is well fitted to the measured data. The same result was obtained by Garcia-Del-Pino in Spain at 50 GHz [21]. In Finland, Salonen [22] compared the ITU-R model with the measured data from satellite link at a low elevation angle (12.7°).…”
Section: Fade Slope Modelssupporting
confidence: 62%
See 2 more Smart Citations
“…where A= 1,2,3,4, … dB. For example, the 2 dB distribution is obtained considering all fade slopes calculated for attenuation A(t) between 1.5 and 2.5 dB [7,19]. Figure 1 shows the CPDF at selected attenuation levels of 1, 3, 5, 10 and 15 dB for the microwave links operating at 15, 23 and 38 GHz.…”
Section: Results and Analysismentioning
confidence: 99%